OPTIMIZING THE USE OF ARTIFICIAL INTELLIGENCE FOR THE CREATION OF PROMOTIONAL CONTENT AND LEARNING IN THE BOARDING SCHOOL - Taufik, Taufik; Effendy, Faried; Purbandini, Purbandini; Purwanti, Endah; Werdiningsih, Indah; Nuzulita, Nania; Baihaqi, Joevans Mikail; Adhipratama, Javier Ihsan; Alfath, Muhammad Fauzan; Pratama, Muhammad Fadhil Putra; Muid, Faruq Abdul; Kastur, Annita; Agustin, Dewien Nabila (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
Darul Ittihad Islamic Boarding School (Pondok Pesantren Darul Ittihad), as a traditional educational institution, faces challenges in optimizing the use of information technology, particularly Artificial Intelligence (AI), for the development of promotional and instructional content. This community service program (PKM) aims to enhance the pesantren's capacity to utilize AI and digital design applications such as Canva. The activity was conducted in three phases: preparation, implementation, and evaluation. During the preparation phase, the team conducted a needs assessment survey and developed relevant training materials. The implementation phase consisted of two training sessions, focusing on the creation of AI-based promotional and educational content. Evaluation was carried out by collecting participant feedback through a questionnaire distributed via Google Forms. The evaluation results indicated a high level of participant satisfaction, with an average score of 3.24 out of 4. Additionally, 88% of participants successfully completed the independent assignments provided after the training, demonstrating a significant improvement in skills. This program concludes that the integration of AI into teaching and promotional processes at Darul Ittihad has the potential to enhance communication effectiveness, increase content relevance, and better prepare students to face the challenges of the digital era.